KEEFEKTIFAN MODEL KEPALA BERNOMOR STRUKTUR DENGAN MEDIA ZIG-ZAG TERHADAP KETERAMPILAN MENULIS PANTUN SISWA KELAS V - Maimunia Rizqi Aulia; Nugraheti Sismulyasih Sb (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research aimed to determine the effectiveness of structured numbered head model using zig-zag media to poem writing skills of class V Gugus Arjuna State Elementary School, Semarang City. This research belongs to quantitative research which has type of experimental research using Quasi Experimental Design and applied Nonequivalent Control Group form. The subjects of this research were students of class V Gugus Arjuna State Elementary School, SemarangCity. The samples of this research were students of Class VA Krobokan State Elementary School as control class and students of class VB as experimental class. Sampling technique was used area sampling. Data gathering technique was used documentation and test. The research data result was analyzed by using prerequisite test and hypothesis test. The study data result were analyzed using t- test and n-gain test. The result of the hypothesis test showed thatt(calculate) 1.6927 > t(tabel) 1.66. N-gain control class 0.132 (low) and experimental class 0.320 (medium). From the analysis it can beconclude that structured numbered head learning model using zig-zagmedia is effective to poem writing skill of class V Gugus Arjuna State Elementary School, Semarang City.